EFFECT OFCHEMICAL FERTILIZERS LEVELS (NPK) ON THE GROWTHAND FLOWERING OF TWO VARIETY OF TULIP ( Tulipa gesneriana). - Ismael , Bairam Solomon (Diyala Agricultural Sciences Journal, 2013)
The experiment was done in green house (not heated) at the department of Horticulture and landscape / college of Agriculture – University of Tikrit from November 2011 to May 2012 on two varieties of tulip , first Whit lily flowering and second Red Frenged. Different levels of NPK 15:15:15 were used (0 , 80 gm , 120 gm)/m2. Randomized complete black design was used with three replications. The results showed that variety Frenged was higher in total plant length , chlorophyll percent , length of flower stalk and diameter; 46.97 cm , 66.51 SPAD , 43.33 cm and 4.63 mm respectively . while fertilizer level F2 was higher in many character is tics of flowering growth as the flower stalk diameter and flower diameter which was 4.41mm and 14.29 mm .